Application Of Potassium Fertilizer and Teak Leaves Debris for Arrowroot Yield - Ahmad Ichsan Yunanto; Supriyono Supriyono; Sri Nyoto (Perkumpulan Agroteknologi/Agroekoteknologi Indonesia, 2017)
Arrowroot yield can be used as a substitute for rice. Arrowroot tubers can be utilized to meet the needs of carbohydrates. Potassium fertilizer can help the formation of arrowroot tubers and the formation of arrowroot starch. Arowroot are found wildly grown under teak. This research aims to determine the dose of potassium fertilizer and determine the influence of teak leaf debris on arowrrot yield. This research was held from March to September 2016 in the Agricultural Land UNS Jumantono. The research using Randomized Completely Block Design (RCBD) method. Two separate experiments that KCl fertilizer application and the application of teak leaf debris dry. KCl fertilizer treatment given to the arrowroot plant is K0 (0 g-1plant), K1 (2,4 g-1plant), K2 (4,8 g-1plant), K3 (7,2 g-1plant) and K4 (9,6 g-1plant). Debris leaves of teak treatment given the arrowroot plant is A0 (0 g-1plant), A1 (20 g-1plant), A2 (40 g-1plant), A3 (60 g-1plant) and A4 (80 g-1plant). The results showed that the fertilizer KCl 4,8 g-1plant tends to increase arrowroot yields. Adding teak leaf debris 80 g-1plant tends to increase the number and weight of arrowroot tubers.